Oral manifestations of celiac disease - Pastore, Luca; Carroccio, Antonio; Compilato, Domenico; Panzarella, Vera; Serpico, Rosario; Lo Muzio, Lorenzo (Journal of clinical gastroenterology, 2008)
Contrary to early beliefs, celiac disease (CD) is relatively common; however, it still remains underdiagnosed since most cases are atypical, with few or no gastrointestinal symptoms and predominance of extraintestinal manifestations. As a consequence, the diagnosis of the disorder often requires a multidisciplinary approach. Also some oral ailments have been described in celiac patients. In this study, we review the papers that have reported oral manifestations in subjects with CD. A comprehensive literature search was conducted in Medline and Embase databases using appropriate key words. Additional papers were selected by cross-referencing from the retrieved articles. Dental enamel defects are the oral lesions most closely related to CD. There are conflicting data on the association between CD and recurrent aphthous stomatitis. A correlation of CD with atrophic glossitis has been reported, although robust evidence in support of it is lacking. Patients with CD have caries indexes seemingly lower than healthy individuals, but they may experience delay in tooth eruption. Occurrence of other oral mucosal lesions in CD subjects is likely occasional. Patients with systematic dental enamel defects should be screened for CD even in the absence of gastrointestinal symptoms. CD screening tests for patients with oral aphthae or idiopathic atrophic glossitis should be selectively considered during a medical evaluation that focuses on all aspects of the patient's status.